2013
DOI: 10.4025/cienccuidsaude.v12i2.18407
|View full text |Cite
|
Sign up to set email alerts
|

<b>O idoso hospitalizado: atuação do acompanhante e expectativas da equipe de enfermagem</b> DOI: 10.4025/cienccuidsaude.v12i1.18407

Abstract: RESUMO Este estudo objetivou descrever as atividades realizadas pelos acompanhantes de idosos hospitalizados e as expectativas da equipe de enfermagem quanto a esses acompanhantes. Estudo transversal analítico, realizado em um hospital universitário, em Montes Claros, Minas Gerais, Brasil, com 30 acompanhantes de idosos e 32 profissionais de enfermagem, teve como instrumento de coleta de dados um questionário elaborado com referenciais de autores estudiosos da temática. Utilizou-se na análise de dados o teste … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…Estudos realizados com idosos hospitalizados no Rio de Janeiro e em Minas Gerais também evidenciaram maior proporção de acompanhantes do sexo feminino (TEIXEIRA et al, 2013;CHERNICHARO & FERREIRA, 2015). Estudo sobre idosos verificou que o grupo dos acompanhantes é composto na maioria das vezes por esposa e filhas (FERREIRA et al, 2014).…”
Section: Resultsunclassified
“…Estudos realizados com idosos hospitalizados no Rio de Janeiro e em Minas Gerais também evidenciaram maior proporção de acompanhantes do sexo feminino (TEIXEIRA et al, 2013;CHERNICHARO & FERREIRA, 2015). Estudo sobre idosos verificou que o grupo dos acompanhantes é composto na maioria das vezes por esposa e filhas (FERREIRA et al, 2014).…”
Section: Resultsunclassified
“…The presence of a companion during hospitalization is a right of elderly persons, with such an individual assuming a co-caregiver role in this environment, in partnership with the health team. 27,28 It is therefore extremely important to identify the knowledge and practices of such persons, as they are partners in caring for the elderly, even in hospitals. 28,29 Despite the small sample size and the limitation of being performed in a single department of a public hospital, the results of this study identify relevant characteristics of the application of OIT among the elderly, as well as the knowledge of their companions, enabling the formulation of strategies related to OIT when used with this population group.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the highlighted speeches we observed that the presence of the companion is affirmed as necessary to collaborate with the nursing care. 12 Therefore, it is essential ethical-legal training of the nursing professional to understand the limits of their performance and the companion of the elderly. It is only through this understanding that it will be possible…”
Section: Nursing Care For Hospitalized Elderly Faces Limits and Diffimentioning
confidence: 99%